Pengaruh Model Direct Instruction Terhadap Keterampilan Bermain Dalam Kegiatan Ekstrakurikuler Bola Voli Siswa Sekolah Menengah Atas - Adinda Artamevia Y; Febi Kurniawan; Ega Rahayu (Peneliti.net, 2022)
The purpose of this study was to determine the effect of the Direct Instruction Model on playing skills in volleyball extracurricular activities for SMAN 12 Jakarta students. To find out whether there is an effect of Direct Instruction Mode on Playing Skills in volleyball extracurricular activities. The research method used in this study is the experimental method. The design or design in this study uses one group pretest posttest design. The population in this study were 29 students. The sample selection used purposive sampling by taking samples, namely new school year students who this year had just taken part in volleyball extracurricular activities. The number of research samples was 12 students. The results of the paired sample t-test in the experimental group showed significant results of 0.000 and the mean pretest value was 62.75 and the mean posttest value was 74.25, there was a difference of 11.5 between the pretest value and the posttest value, indicating that there was such an influence it can be concluded, that the Direct Instruction Model improves playing skills in volleyball extracurricular activities